HUBUNGAN RESIKO DAN TINGKAT KEUNTUNGAN DALAM KONTEKS PORTOFOLIO PASAR MODAL INTERNASIONAL: PENGAMATAN TERHADAP BEBERAPA BURSA EFEK ASIA PASIFIK DAN SEKURITAS YANG DIPERDAGANGKAN DI BURSA EFEK JAKARTA - AGUS SARTONO; SUKASMANTO SUKASMANTO (Faculty of Economics and Business, Universitas Gadjah Mada, 1997)
During the last five years, relationship between risk and profit in stockexchange markets in the Asia Pacific regions was found to be integrated with international stock exchange market portfolio, with the exception of Wellington-New Zealand stock exchange market. Annual analyses have shown that the relationship does not show a tendency to either become more integrated or more segmented, but instead tend to be fluctuating. From the point of view of Indonesian investors, relationship between risk and profit level in Asia Pacific stock exchange markets are more valued because the Rupiah is currently weak against all Asia Pacific currencies.In specific, analysis of portfolio, group according to risk levels, which are traded in Jakarta Stock Exchange demonstrates that in general relationship between risk and profit level does not occur in International and domestic stock exchange portfolios.